Half Logistic Generalized Inverse Rayleigh distribution for modeling Breast Cancer data - Oseghale*†, O.I.; Micah†, E. S. (International Journal of Mathematical Analysis and Modelling, 2025)
This article introduced a three-parameter extension of the Generalized Inverse Rayleigh distribution called half-logistic Generalized Rayleigh distribution, which has sub-models the Generalized Rayleigh and Rayleigh distribution. The proposed model is quite flexible and adaptable to model any kind of life-time data. Its probability density function may sometimes be unimodal and its corresponding hazard rate may be of monotone or non-monotone shape. Standard statistical properties such as it ordinary and incomplete moments, quantile function, moment generating function, reliability function, Lorenz and Bonferroni curves. The maximum likelihood method is used to obtain the estimates of the model parameters. An application of the newly developed model to breast cancer data is presented.